The evolution of prey‐wrapping behaviour in spiders - Barrantes Montero, Gilbert (2007)
We traced the evolution of silk use by spiders in attacks on prey by combining previous publications with new observations of 31 species in 16 families. Two new prey‐wrapping techniques are described. One, in which the spider holds a tense line (often covered with viscid silk) with both legs IV and applies it to the prey with a simultaneous movement of both legs, may be a synapomorphy linking Theridiidae, Nesticidae, and Synotaxidae. The other, in which the spider stands over the prey and turns in place, is apparently very ancient; it occurs in Theraphosidae, Tengellidae, and Agelenidae. The use of legs IV to wrap prey is described for the first time in Filistatidae and Scytodidae. Using a recent phylogeny of spiders, we propose that prey wrapping with legs IV has evolved convergently at least four times. We propose that prey wrapping originally evolved from egg‐sac construction behaviour.